Entrepreneurial attitude in urban and rural youth in two regions of Colombia - RIVERA LOZADA, ISABEL CRISTINA; MENESES MEDINA, PAULA ANDREA; LOZADA, ORIANA RIVERA (International Journal of Psychosocial Rehabilitation, 2020)
In Colombia, as in the rest of the world, the youth unemployment rate is higher than the global unemployment rate. This research aimed to contrast the entrepreneurial attitude of a group of students at five schools in two regions of the country. The methodological approach was quantitative and descriptive, contrasting the entrepreneurial attitude of students in urban areas with attitudes in rural areas, as well as with each school. The results showed that in urban areas there is greater participation of students with a high level of entrepreneurial potential and lower participation of students with low level in comparison to rural areas.